2007
DOI: 10.1080/02701367.2007.10599421
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Support, Work-Family Conflict, and the Job-Life Satisfaction of University Coaches

Abstract: This study examined the relationship between organizational support, work-family conflict, and job and life satisfaction among coaches. Data from collegiate head coaches with families (N = 253) were gathered through a mailed questionnaire. Results from a series of covariance structure models indicated that a partially mediated model was the best fitting model, chi2 = (255, N = 253) 461.20, p <. 001; root mean error of approximation = . 05; comparative fit index = .95; parsimonious normed fit index = .71. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 51 publications
7
84
1
3
Order By: Relevance
“…Their findings found support for the mediation effects of job satisfaction. Further, in an investigation of university coaches with families, Dixon and Sagas (2007) found that the relationship between organizational supports and life satisfaction was mediated by job satisfaction, and Yousef (2002) found that job satisfaction mediated the relationship between role conflict and organizational commitment in a sample of employees in the UAE.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their findings found support for the mediation effects of job satisfaction. Further, in an investigation of university coaches with families, Dixon and Sagas (2007) found that the relationship between organizational supports and life satisfaction was mediated by job satisfaction, and Yousef (2002) found that job satisfaction mediated the relationship between role conflict and organizational commitment in a sample of employees in the UAE.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, these findings are important to consider because most involved professionals engaged in stressful occupations. For example, in an investigation of university coaches with families, Dixon and Sagas (2007) found that the relationship between organizational supports and life satisfaction was mediated by job satisfaction. The same study also found that the relationship between organizational supports and life satisfaction was fully mediated through work -family conflict and job satisfaction.…”
Section: Job Satisfaction As a Mediatormentioning
confidence: 96%
“…However, other participants (e.g., Darlene, Melanie, Karla, Jane) highlighted examples of how their employers took the initiative and approached them with supportive words, and even measures (e.g., flexible scheduling, additional staff) to ease the transition. This type of initiative would certainly be an example of what Fink et al (2001Fink et al ( , 2003 call "proactive diversity management strategies" (Cunningham and Fink 2006, p. 459) that can lead to both positive individual and organizational outcomes (see also Dixon and Sagas 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Questions followed an interview guide (see Appendix A) that was developed from previous literature in the areas of life course theory (Sweet and Moen 2006) and work-family conflict (e.g., Allen et al 2000;Bruening 2005, 2007;Dixon and Sagas 2007;Netemeyer et al 1996), and gender studies in sport (Inglis et al 2000;Knoppers 1992;Shaw and Frisby 2006). Participants were first asked a range of biographical/social context questions including tracing their own and their family of origin's involvement with sport and their own career progression.…”
Section: Interviewsmentioning
confidence: 99%
“…The positions left vacant by women are oftentimes filled by men (Hart et al 1986), thereby serving to further increase the discrepancies in the proportion of men and women serving as head coaches. In seeking to understand why such differences exist, researchers have pointed to differences between men and women in self-efficacy Cunningham et al 2003), the anticipated outcomes associated with being a head coach ), support from administrators (Dixon and Sagas 2007), perceived opportunities in the profession (Knoppers et al 1991), and the Title IX compliance of the department in which the coach works (Sagas and Batista 2001).…”
Section: Micro Level Forcesmentioning
confidence: 97%